Pelaksanaan Undang-undang Nomor 28 Tahun 2014 tentang Hak Cipta Terkait Penggandaan Buku pada Usaha Fotokopi Cahya Printing Bali - Ni Luh Dwi Ega Mileniawati; Nella Hasibuan OLeary; Desak Gde Dwi Arini (Jurnal Preferensi Hukum, 2021)
The essence of national development is the development of the whole human being and the development of the entire Indonesian society based on Pancasila and the 1945 Constitution of the Republic of Indonesia. Development is not only pursuing physical or mental progress, but also pursuing harmony, harmony and balance. The purpose of this study is to determine the implementation of Law Number 28 of 2014 concerning Copyright related to illegal copying of books in the Cahya Printing Bali photocopy business and to find out legal protection for book creators related to illegal book duplication in the Cahya Printing Bali photocopy business. The research method used is to use the empirical legal research method, which is to study the legal provisions that apply or what happen in reality in society. The results of the study show that the implementation of Law Number 28 of 2014 concerning copyright related to illegal book duplication in the Cahya Printing Bali photocopy business has not been carried out due to lack of support from related parties, namely still weak policing and lack of socialization. Legal protection for book creators related to the copying of illegal books in the copy business of Cahya Printing Bali in protecting creators' rights, the government does not provide direct legal protection.